2019
DOI: 10.1177/1468087419878911
|View full text |Cite
|
Sign up to set email alerts
|

Novel approach for adaptive coefficient tuning for the simulation of evaporating high-speed sprays injected into a high-temperature and high-pressure environment

Abstract: Producing reliable in-cylinder simulations for quick-turnaround engine development for industrial purposes is a challenging task for modern computational fluid dynamics, mostly because of the tuning effort required for the sub-models used in the various frameworks (the Reynolds-averaged Navier–Stokes and large eddy simulation). Tuning is required because of the need for modern engines to operate under a wider range of conditions and fuels. In this article, we suggest a novel methodology based on automated simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 71 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…6 An excellent review of different LES modeling approaches can be found in the literature by Pope. 20 Nsikane and et al, 21 in a study published in 2019, studied the effect of different turbulence models on hightemperature diesel spray. In this study, the effect of different constants on the penetration depth of the spray was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…6 An excellent review of different LES modeling approaches can be found in the literature by Pope. 20 Nsikane and et al, 21 in a study published in 2019, studied the effect of different turbulence models on hightemperature diesel spray. In this study, the effect of different constants on the penetration depth of the spray was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 In fact, combustion knock is a major barrier in achieving higher thermal efficiency in SI engines [1][2][3][4][5][6][7] Performance of a gasoline/ alcohol blend fuelled direct injection SI engine significantly depends on fuel spray phenomenon, therefore recently many researchers have focused on resolving this issue. [8][9][10][11][12] Also, understanding spray characteristics of both 'gasoline' and 'renewable fuels' has become very important. 13,14 Parameters that improve fuel-air mixing characteristics in internal combustion (IC) engines include spray atomization, droplet sizevelocity distribution and evaporation characteristics of the fuels.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] Given the limited quantitative information around the flow structure inside diesel injectors, fuel injection equipment manufacturers require robust predictive Computational Fluid Dynamics (CFD) tools, in order to understand the physical mechanisms taking place during injection. From a physical viewpoint, modelling of such flow conditions requires the fluid compressibility 24 , mass transfer (cavitation, flash boiling, evaporation 25,26 ) and heat transfer [27][28][29] to be taken into account, which increase the complexity as well as the computational cost of the simulations. Additionally, the fluid dynamics processes occur at high Reynolds number and therefore accounting for the effect of turbulent structures and vortex dynamics, is key in explaining how the injected fuel spray is formed [30][31][32][33][34] ; this can only be resolved using very fine computational grids and scale resolving simulations, such as Large Eddy Simulation (LES), as initially presented in 35 for nozzle flows.…”
Section: Introductionmentioning
confidence: 99%